Apple F-Box Protein MdMAX2 Regulates Plant Photomorphogenesis and Stress Response - An, Jian-Ping; Li, Rui; Qu, Feng-Jia; You, Chun-Xiang; Wang, Xiao-Fei; Hao, Yu-Jin (Frontiers in Plant Science, 2016)
MAX2 (MORE AXILLARY GROWTH2) is involved in diverse physiological processes, including photomorphogenesis, the abiotic stress response, as well as karrikin and strigolactone signaling-mediated shoot branching. In this study, MdMAX2, an F-box protein that is a homolog of Arabidopsis MAX2, was identified and characterized. Overexpression of MdMAX2 in apple calli enhanced the accumulation of anthocyanin. Ectopic expression of MdMAX2 in Arabidopsis exhibited photomorphogenesis phenotypes, including increased anthocyanin content and decreased hypocotyl length. Further study indicated that MdMAX2 might promote plant photomorphogenesis by affecting the auxin signaling as well as other plant hormones. Transcripts of MdMAX2 were noticeably up-regulated in response to NaCl and Mannitol treatments. Moreover, compared with the wild type, the MdMAX2-overexpressing apple calli and Arabidopsis exhibited increased tolerance to salt and drought stresses. Taken together, these results suggest that MdMAX2 plays a positive regulatory role in plant photomorphogenesis and stress response.